การใช้กระบวนการแก้ปัญหาและโปรแกรม App Inventor พัฒนาทักษะการคิดเชิงคำนวณ (Computational Thinking: CT) สำหรับผู้เรียนระดับมัธยมศึกษา - คีรีรัตน์, ชยการ (Journal of Education Studies, Chulalongkorn University, 2019)
Computational thinking skills constitute a problem solving process that can be applied in many fields – science, technology, mathematics, the humanities, and sociology. Indeed, it is an important tool in developing a computer program, and students can learn to develop a computer program that can enhance their computational thinking. However, writing a computer program with the available programs written in English is difficult for both students and novices. App Inventor is a program designed for students so that they are able to write a program even though they are not good at English. Instead of using English, this program uses pictures or icons to facilitate students when they write a program. This will help them learn more effectively. Also, they can plan the solution and test the process that they designed without any hindrance on learning command structure. In addition, App Inventor can also be operated on mobile devices such as mobile phones; consequently, students can apply what they have learnt to their real lives and integrate it into other sciences. The hands-on experience can enhance students’ learning, creativity and problem-solving skills, so eventually they can become experienced or professional programmers.